PENGARUH GAYA KEPEMIMPINAN KAPOLSEK TERHADAP KINERJA ANGGOTANYA DI POLSEK WONOBOYO KABUPATEN TEMANGGUNG - Marinda. W, Vuvud; Rahmawati, Rita; Salbiah, Euis (JURNAL GOVERNANSI, 2016)
Police sector (police) Wonoboyo an element of the duties and authority of the law of the District Police region Wonoboyo Temanggung regency, Central Java province which is an extension of the internal security duty Police Resort (Police). Noted region Wonoboyo police law in 2016 to the month of February there were 5 cases consisting of 4 times the theft as well as the first time fraud. Thus, only 36.97% of cases that can be resolved by the Police Criminal Investigation Unit Wonoboyo, or in other words the police officer performance Wonoboyo still low. The method used in this research is quantitative approach to research is descriptive, the research focused on solving the problem was investigated by using file state the subject or object of research is happening now based on factors that seen in the field as it should be or is used to describe a fact or systematic character defined population, actual and precise. The results of this study indicate that the leadership style adopted by the Chief of Police Sector Wonoboyo obtained 3.68 figure with a good assessment criteria. While the performance results obtained with the 4.50 figure Excellent assessment criteria. It is clear that the leadership style adopted by the Chief of Police Sector Wonoboyo obtained 3.68 figure with a good assessment criteria. This is influenced by leadership style (10.4%) and (89.6%) by other factors, such as motivation, supervision, etc., but not studied. The conclusion of this research in general is a style of leadership, the Chief of Police Sector Wonoboyo considerable influence despite the need for improvement especially in terms of giving confidence to subordinates to make decisions and give freedom to members to cooperate with other units.Â Keywords: leadership style, performance, Police.